Proceso atención de enfermería en gestante de 24 semanas con preeclampsia. - Fuentes Muñoz, Diana Narcisa (2022)
Preeclampsia is one of the main hypertensive disorders typical of pregnancy, in some cases it is usually silent and its symptoms are obvious to us. This pathology is characterized by the presence of proteinuria in the urine and arterial hypertension above 140/90 mmHg, it is evident after 20 weeks of gestation, at delivery or 2 weeks after delivery. An exact cause of preeclampsia is not yet known, but nevertheless some studies have considered genetic, immunological, nutritional, endocrine, and nutritional factors as a possible cause. Preeclampsia is considered a public health problem due to the causes of maternal and perinatal death throughout the world, according to data from the World Health Organization, it can be seen that the incidence ranges between 2 and 10% of all pregnancies, and its prevalence is seven times higher in developing countries than in developed countries. In Ecuador in a report from the Gazette of the Ministry of Public Health in 2021 of 35%. In the present clinical case, it was performed on a pregnant patient of 24 weeks of gestation with preeclampsia, due to arterial hypertension of 150/90 mmHg, proteinuria in urine (+++), edema in the lower extremities and mild headache. Once the nursing assessment was carried out, a nursing care plan was planned with the aim of restoring the patient's health and avoiding complications.